Primary Nursing: an Emerging approach for Nursing Care Delivery In Nigeria (2009)
Health care delivery system has evolved over time as a result of changes in the economy and increasing consumer awareness. This has resulted in many health professions trying various frameworks for delivery of care to ensure cost effective care and consumer satisfaction. Nursing has tried various frameworks of care delivery ranging from task oriented, team nursing, case nursing, Primary nursing etc. Each institution uses the method that is suitable and easily implemented. Of all the methods, primary nursing is the one that seems quite promising in the drive to achieve the goal of providing quality care and client satisfaction. Primary nursing is defined as a management system in which the professional nurse assumes full responsibility for total patient care for a small number of clients. It is seen as a way of thinking and working with patients that challenges out dated traditional nursing hierarchies and support the way forward for professional nursing. Its advantages include consistency and continuity of care, client satisfaction, increased professional autonomy, job satisfaction and improvement in quality of nursing care. The disadvantages are difficulty in implementation, which could result from not having enough adequately prepared nurses who are ready to take up the responsibility Primary nursing framework is yet to be tried and implemented in most hospitals in Nigeria. It has been tried and found suitable where it was tested but it is yet to be embraced by nurses generally in Nigeria. It is emerging in Nigeria, and there is need to increase awareness about this framework so that it can be further explored as it is quite promising in moving nursing forward as it ensures professional autonomy, accountability and job satisfaction for nurses. In conclusion, since this model is a way of moving the profession forward and improving client care, there is need to carry out objective analysis and put modalities in place for the implementation of this model to ensure client satisfaction and job satisfaction as well as professional growth.